Manajemen Projek Penguatan Profil Pelajar Pancasila Untuk Meningkatkan Karakter Peduli Lingkungan: Project Management Strengthening Pancasila Student Profiles to Improve Environmentally Caring Character - Suyitno, Suyitno; Sholeh, Muhamad; Khamidi , Amrozi (Thawalib: Jurnal Kependidikan Islam, 2024)
Character education in schools forms a responsible and ethical generation, as well as instilling awareness and behavior to care for the environment in a global and national context. This study aims to examine the Management of the Pancasila Student Profile Strengthening Project at State Junior High School 1 Kenduruan, Tuban Regency. This study uses a qualitative method with a case study approach to analyze the implementation of the Pancasila Student Profile Strengthening Project in building environmental care character. Data was collected through interviews, observations, and documentation analysis, then processed using condensation techniques, presentation, and conclusion drawn. The validity of the data is guaranteed through triangulation of sources and methods. The results of the study show that (1) Project Management for Strengthening the Pancasila Student Profile: Program management is carried out through the formation of a team of facilitators, designing theme dimensions, preparing teaching modules based on student needs, and implementing structured action-based learning to support the character of caring for the environment according to the vision of Adiwiyata School. Continuous evaluation is carried out using formative and summative assessments. (2) Impact of implementation: The implementation of the program increases students' awareness of environmental issues, practical skills in waste management, strengthening Pancasila values such as responsibility and mutual cooperation, and the creation of environmentally friendly habits that are oriented towards sustainability. The school gained recognition as an environment-based learning model. (3) Solutions to overcome obstacles: Strategies include teacher training, evaluation system modification, collaborative learning, resource optimization, and collaboration between schools to share best practices. Focus on the involvement of all elements of the school to ensure the sustainability of the program and the achievement of the vision of Adiwiyata School.